Evaluation of the antimicrobial and cytotoxic effect of Dendranthemaindicum (L Desmoul ) leave extract - H, Momoh,; M.M, Idris; O.A, Adoum, (IJRDO-Journal of Applied Science, 2017)
Hexane, chloroform, ethyl acetate and ethanol extracts of Dendranthema indicum leaf were studied for their cytotoxic effect and antimicrobial activities against seven human pathogenic bacteria Shigella dysenteriae, Salmonella typhi, klebsiella pneumonia, Staphylococcus aureus, proteus mirabilis, Escericia coli and pseudomonas aeriginosa,) using disc diffusion method. All the extracts exhibited moderate to good antibacterial activity against all the pathogens tested except proteus mirabilis and Salmonella typhi, The chloroform extract exhibited the largest zone of inhibition (20 mm) against Staphylococcus aureus.The ethyl acetate extracts exhibited the highest lethality on brine shrimp larvae at LC 50 values 211.6. (LC 50 ) were determined at 95% confidence intervals by analyzing the data on a computer loaded with “Finney Programme.”